Preclinical Drug Discovery in Colorectal Cancer: A Focus on Natural Compounds - Rahman, Heshu S. (Current Drug Targets, 2021)
Background: Colorectal cancer (CRC) is considered one of the most predominant and deadly cancer globally. Nowadays, the main clinical management for this cancer includes chemotherapy and surgery; however, these treatments result in the occurrence of drug resistance and severe side effects, and thus it is a crucial requirement to discover an alternative and potential therapy for CRC treatment. Numerous therapeutic cancers were initially recognized from natural metabolites utilized in traditional medicine, and several recent types of research have shown that many natural products own potential effects against CRC and may assist the action of chemotherapy for the treatment of CRC. It has been indicated that most patients are well tolerated by natural compounds without showing any toxicity signs even at high doses. Conventional chemotherapeutics interaction with natural medicinal compounds presents a new feature in cancer exploration and treatment. Most of the natural compounds overwhelm malignant cell propagation by apoptosis initiation of CRC cells and arresting of the cell cycle (especially at G, S, and G2/M phase) that result in inhibition of tumor growth. Objective: This mini-review aimed to focus on natural compounds (alkaloids, flavonoids, polysaccharides, polyphenols, terpenoids, lactones, quinones, etc.) that were identified to have anti- CRC activity in vitro on CRC cell lines and/or in vivo experiments on animal models. Conclusion: Most of the studied active natural compounds possess anti-CRC activity via different mechanisms and pathways in vitro and in vivo that might be used as assistance by clinicians to support chemotherapy therapeutic strategy and treatment doses for cancer patients.
Keywords: drug discovery